ANALISIS RHODAMIN B PADA SEDIAAN LIPSTIK DAN PERONA MATA SECARA KCKT - Dede Komarudin; Siva Fauziah; Ratih Pramintari (STIKIM Press, 2019)
Rhodamin B is a red synthesis dye that is often used in the cat and textile industries, including carcinogens if used and accumulates in the body. Lipstick and eye shadow are a type of decorative cosmetics that have red color in the preparations in large quantities. Based on BPOM findings there is still an examination of rhodamine b in a decorative cosmetic preparation, a study was carried out on the analysis of Rhodamin B. For the collection and calculation of rhodamin B levels in lipstick and eye shadow, the HPLC method was carried out. The mobile phase used was 95% acetonitrile: 20 mM diamonium hydrogen phosphate buffer solution pH 6 (80:20), Gemini C18 column, 548nm PDA detector with a flow rate of 0.71 ml / min. The samples cited were five eye shadow samples and three lipstick samples. Two of the three lipstick samples contained rhodamine B and all of the eye shadow samples contained rhodamine B. The highest level of Rhodamine B in the eye shadow sample was 776.98 mg / kg and the lowest in the lipstick sample was 4.23 mg / kg.